Spontaneous emergence and extinction of resources in distributed systems-Resource Allocation as Evolving Strategy Revisited - Njimolu Anyouzoa, Alain G. (2002)
Many approaches to distributed load balancing focus on algorithms, most of the time leading to centralized mechanisms while trying to solve distributed problems. Olafsson's approach is interesting in that it offers a framework where local decision making is the key to achieving efficient resource allocation. Although he decouples interactions between agents, this loose coupling is lost with the introduction of differentiated pricing strategies and makes the stability analysis around potential equilibria more complex. Furthermore, his model does not provide support for stochastic events in distributed environments. In this paper, we describe a modi fication of his model to address extinction and innovation in the population of resources and present our current experimental directions. This paper is the first installment of a series which will describe the architecture of the system we have built to prove our concepts and provide experimental results.